2021
DOI: 10.20944/preprints202105.0352.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Field Guide to 3D Printing in Microscopy

Abstract: The maker movement has reached the optics labs, empowering researchers to actively create and modify microscope designs and imaging accessories. 3D printing has especially had a disruptive impact on the field, as it entails an accessible new approach in fabrication technologies, namely additive manufacturing, making prototyping in the lab available at low cost. Examples of this trend are taking advantage of the easy availability of 3D printing technology. For example, inexpensive microscopes for education have… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 146 publications
(190 reference statements)
0
8
0
Order By: Relevance
“…Two scientific fields have greatly benefited from the advent of 3D printing and the possibility of rapid prototyping directly in the laboratory: microfluidics [ 23,24 ] and microscopy. [ 25 ]…”
Section: Phase Two: Designingmentioning
confidence: 99%
“…Two scientific fields have greatly benefited from the advent of 3D printing and the possibility of rapid prototyping directly in the laboratory: microfluidics [ 23,24 ] and microscopy. [ 25 ]…”
Section: Phase Two: Designingmentioning
confidence: 99%
“…[19] The increasing complexity and associated costs of experiments, due to the increased use of laboratory equipment, as well as the knowledge required to properly operate all the necessary instruments, make high-throughput research very exclusive. [20,21] In turn, it is particularly challenging to train students to use such methods. [22] Our aim in this work is to prove the principle of lab automation using open, accessible tools, with the ultimate goal of making this technology more widespread and easier to use.…”
Section: Introductionmentioning
confidence: 99%
“…These projects have all been replicated by the growing community of microscopy users. For a great overview of the subject, please refer to Rosario et al [21] In most cases, commercial devices lack open hardware or software interfaces for customization or automation, making it difficult or impossible to use them outside of the intended application for the devices. The Opentrons OT-2 pipetting robot [6,28] which we use in this manuscript is an example of commercially produced open-source hardware.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing complexity of experiments due to technologization, the associated cost of laboratory equipment, and the knowledge required to properly operate all the required instruments make highthroughput research very exclusive. 18,19 In turn, it is particularly challenging to train students to use such methods. 20 In the past, much open-source software and, more recently, open hardware projects have shown that by creating a community of developers and allowing them to develop the projects together, a high level of professionalism and usability is created, with the help being offered free of charge.…”
Section: Introductionmentioning
confidence: 99%
“…For a great overview of the subject, please refer to. 19 In most cases, commercial devices lack open hardware or software interfaces for customization or automation, making it difficult or impossible to use them outside of the intended application for the devices, e.g., within a self-designed biological protocol. The Opentrons OT-2 pipetting robot 6,26 which we use in this manuscript is an example of commercially produced open-source hardware.…”
Section: Introductionmentioning
confidence: 99%